EV POWERTRAIN USING COMPUTER-AIDED CONCEPTION (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2025)
One of the simplest ways to rapidly obtain the main characteristics of an EV (Electric Vehicle) powertrain is by calculating the requested values from resistant forces acting on the vehicle. A powertrain covering the operation area of the vehicle can give satisfaction. The autonomy is sustained by the on-board energy source (battery) and the maximum speed and acceleration performances come from the possibility of establishing and maintaining a maximum current through the battery, power electronics, and electric motor. In this context, the present paper is focused on a possible methodology achieved using a computer-aided conception. After determining the characteristics of each powertrain component using calculation and simulation, the behavior of the EV is analyzed under a complete simulation of the powertrain.DOI: https://doi.org/10.36801/apme.2024.1.10
Keywords: Electric vehicle (EV); Simulation; Electric Powetrain; Electric Drives; Copmputer-aided methodology; instruction methodology